Leishmania donovani Nucleoside Hydrolase (NH36) Domains Induce T-Cell Cytokine Responses in Human Visceral Leishmaniasis - Barbosa Santos, Micheli Luize; Nico, Dirlei; de Oliveira, Fabrícia Alvisi; Barreto, Aline Silva; Palatnik-de-Sousa, Iam; Carrillo, Eugenia; Moreno, Javier; de Luca, Paula Mello; Morrot, Alexandre; Rosa, Daniela Santoro; Palatnik, Marcos; Bani-Corrêa, Cristiane; et al. (Frontiers in Immunology, 2017)
Development of immunoprotection against visceral leishmaniasis (VL) focused on the identification of antigens capable of inducing a Th1 immune response. Alternatively, antigens targeting the CD8 and T-regulatory responses are also relevant in VL pathogenesis and worthy of being included in a preventive human vaccine. We assessed in active and cured patients and VL asymptomatic subjects the clinical signs and cytokine responses to the Leishmania donovani-nucleoside hydrolase NH36 antigen and its N-(F1), central (F2) and C-terminal (F3) domains. As markers of VL resistance, the F2 induced the highest levels of IFN-γ, IL-1β and TNF-α and, together with F1, the strongest secretion of IL-17, IL-6 and IL-10 in DTH+ and cured subjects. F2 also promoted the highest frequencies of CD3+CD4+IL-2+TNF-α-IFN-γ-, CD3+CD4+IL-2+TNF-α+IFN-γ-, CD3+CD4+IL-2+TNF-α-IFN-γ+and CD3+CD4+IL-2+TNF-α+IFN-γ+ T cells in cured and asymptomatic subjects. Consistent with this, the IFN-γ increase wascorrelated with decreased spleen (R= -0.428, p = 0.05) and liver sizes (R = -0.428, p = 0.05) and with increased hematocrit counts (R = 0.532, p = 0.015) in response to F1 domain, and with increased hematocrit (R = 0.512, p 0.02) and hemoglobin counts (R = 0.434, p = 0.05) in response to F2. Additionally, IL-17 increases were associated with decreased spleen and liver sizes in response to F1 (R= -0.595, p = 0.005) and F2 (R = -0.462, p = 0.04). Conversely, F1 and F3 increased the CD3+CD8+IL-2+TNF-α-IFN-γ-, CD3+CD8+IL-2+TNF-α+IFN-γ- and CD3+CD8+IL-2+TNF-α+IFN-γ+ T cell frequencies of VL patients correlated with increased spleen and liver sizes and decreased hemoglobin and hematocrit values. Therefore, cure and acquired resistance to VL correlate to the CD4+-Th1 and Th-17 T-cell responses to F2 and F1 domains. Clinical VL outcomes, in contrast, correlate to CD8+ T-cell responses against F3 and F1, potentially involved in control of the early infection. The in silico predicted NH36 epitopes are conserved and bind to many HL-DR and HLA and B allotypes. No human vaccine against Leishmania is available thus far. In this investigation, we identified the NH36 domains and epitopes that induce CD4+ and CD8+ T cell responses, which could be used to potentiate a human universal T-epitope vaccine against leishmaniasis.